Fluctuations and interrelationship of oxidative stress and hepcidin during the menstrual cycle - Yoshida, Ena; Hayashida, Harumi; Shimizu, Tomomi; Cox, Amanda J.; Suzuki, Katsuhiko (Frontiers in Endocrinology, 2025)
BackgroundMenstruation is a daily opportunity for iron loss in women. Hepcidin (Hepc), a key regulator of iron metabolism, is known to respond to both iron status and inflammation. Menstruation is also accompanied by local and systemic production of reactive oxygen species and inflammatory responses. However, fluctuations in Hepc and oxidative stress during the menstrual cycle and their relationship are unclear. The purpose of this study was to clarify of the fluctuations Hepc and oxidative stress and relationships.MethodsSixteen women were recruited, of whom twelve with normal menstrual cycles were included in the final analysis. Blood samples were collected at four time points — The menstrual phase (MP), follicular phase (FP), early luteal phase (ELP), and late luteal phase (LLP) — while the participants were at rest. Serum Hepc, serum ferritin (FER), and oxidative stress levels were evaluated. In addition, differences between the iron-deficient (ID, <12 ng/ml) and non–iron-deficient (NID, ≥12 ng/ml) groups, classified according to FER levels during the ELP, were examined.ResultsOxidative stress showed significant fluctuations across the menstrual cycle (p < 0.01), with higher values during the MP and FP compared with the LLP. This trend was particularly pronounced in the ID group. Hepc did not exhibit significant cyclical fluctuations. Nevertheless, its mean level was highest in the MP and lowest in the FP. No significant correlation was observed between oxidative stress and Hepc. FER was positively correlated with Hepc only in the LP (r = 0.769, p = 0.043), and significant differences in Hepc levels between the ID and NID groups were observed exclusively in the ELP (p = 0.003) and LLP (p = 0.010).ConclusionOxidative stress fluctuated across the menstrual cycle, with increases observed during the MP and FP. These fluctuations appeared to be more pronounced in the presence of ID. In contrast, Hepc did not exhibit consistent cyclical changes. Although oxidative stress was considered to influence Hepc elevation through inflammatory responses, no direct relationship was detected at the blood marker level.